$\begin{array}{l} \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 12 x +6 y =7\\ 16 x +6 y = 4 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 12 x +6 y =7\\ II \qquad 16 x +6 y = 4 \\ I \qquad 12 x +6 y =7 \qquad / \cdot4\\ II \qquad 16 x +6 y = 4 \qquad / \cdot\left(-3\right)\\ I \qquad 48 x +24 y =28\\ II \qquad -48 x -18 y = -12 \\ \text{I + II}\\ I \qquad 48 x -48 x+24 y -18 y =28 -12\\ 6 y = 16 \qquad /:6 \\ y = \frac{16}{6} \\ y=2\frac{2}{3} \\ \text{y in I}\\ I \qquad 12 x +6\cdot 2\frac{2}{3} =7 \\ 12 x +16 =7 \qquad / -16 \\ 12 x =7 -16 \\ 12 x =-9 \qquad / :12 \\ x = \frac{-9}{12} \\ x=-\frac{3}{4} \\ L=\{-\frac{3}{4}/2\frac{2}{3}\} \end{array} & \begin{array}{l} \\I \qquad 12 x +6 y =7\\ II \qquad 16 x +6 y = 4 \\ I \qquad 12 x +6 y =7 \qquad / \cdot1\\ II \qquad 16 x +6 y = 4 \qquad / \cdot\left(-1\right)\\ I \qquad 12 x +6 y =7\\ II \qquad -16 x -6 y = -4 \\ \text{I + II}\\ I \qquad 12 x -16 x+6 y -6 y =7 -4\\ -4 x = 3 \qquad /:\left(-4\right) \\ x = \frac{3}{-4} \\ x=-\frac{3}{4} \\ \text{x in I}\\ I \qquad 12 \cdot \left(-\frac{3}{4}\right) +6y =7 \\ 6 y -9 =7 \qquad / +9 \\ 6 y =7 +9 \\ 6 y =16 \qquad / :6 \\ y = \frac{16}{6} \\ y=2\frac{2}{3} \\ L=\{-\frac{3}{4}/2\frac{2}{3}\} \end{array} \end{array} \end{array}$